2020
DOI: 10.5812/aapm.109863
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Near Infra-Red Spectroscopy (NIRS) on Early Diagnosis of Cardiac Surgery-Associated Acute Kidney Injury

Abstract: Background: Cardiac surgery-associated acute kidney injury (CSA-AKI) is a major adverse effect of cardiac surgery. The early detection of this complication can improve the quality of postoperative care and help prevent this phenomenon. Methods: In this prospective descriptive-analytical study, 148 patients were enrolled, 107 of whom were selected for analysis between February and September 2019 in the Cardiac Surgery Unit of Golestan Hospital, Ahvaz, Iran. Kidney tissue oxygen saturation was measured at multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Kidney transplantation is a high-risk surgery that requires hemodynamic monitoring to support goal-directed therapy, but transpulmonary thermodilution is not commonly used in kidney transplant surgery because of the risks posed by PAC insertion. Non-invasive approaches such as the bioimpedance method or near-infrared spectroscopy (NIRS) were proposed for global hemodynamic to regional kidney saturation monitoring to predict perioperative AKI ( 28 ). Bioimpedance cardiometry is a promising non-invasive technique for intraoperative hemodynamic monitoring ( 11 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplantation is a high-risk surgery that requires hemodynamic monitoring to support goal-directed therapy, but transpulmonary thermodilution is not commonly used in kidney transplant surgery because of the risks posed by PAC insertion. Non-invasive approaches such as the bioimpedance method or near-infrared spectroscopy (NIRS) were proposed for global hemodynamic to regional kidney saturation monitoring to predict perioperative AKI ( 28 ). Bioimpedance cardiometry is a promising non-invasive technique for intraoperative hemodynamic monitoring ( 11 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…During CPB, anesthesia was continued with continuous injections of anesthetics. In all patients, an attempt was made to main-tain the hematocrit of patients above 24 to 27%; for this purpose, blood was transfused if necessary (17). For this study, surgeons who used del Nido cardioplegia and had similar routines were used.…”
Section: Methodsmentioning
confidence: 99%
“…There have been several systematic reviews on various types of surgery. These studies have shown the positive role of this technology in preventing neurological complications (26)(27)(28)(29). However, since there is limited information on the use of NIRS in neurosurgical patients, this systematic review was carried out to review studies investigating the use of NIRS in the prevention of neurological complications during neurosurgery and postoperative care.…”
Section: Objectivesmentioning
confidence: 99%